A STUDY OF TEACHERS’ COMPETENCE OF TWO HIGH SCHOOLS INNORTHERN RAKHINE (ARAKAN) STATE, WESTERN MYANMAR - Kavinda, U.; Ye, Yan (Scholar: Human Sciences, 2015)
The main purpose of this study was to compare the teachers’ competence according to their Gender, Age and Education background at Rathedaung High School and Jay Di Pin High School, Northern Rakhine (Arakan) State, Western Myanmar. The collected data were analyzed by using the descriptive statistics, Frequency, Percentage, Standard deviation, Mean, and Independent Sample t-test (Two-tailed). The study found that the teachers’ competences at both schools were perceived as high level. There was no significant difference of teachers’ competence according to their age and education background at Rathedaung High School and Jay Di Pyin High School in Northern Rakhine (Arakan) State, Western Myanmar. However, a significant difference of teachers’ competence according to their gender was found in two schools. The total mean scores for teachers’ competence of Rathedaung high school and Jaydi Pyin high school were 4.632 and 4. 38, both were in the range of 4.50. This implied that the teachers ‘competence at both schools were high. At Rathedaung high school, the highest mean score of teachers’ competence was 4.78 which were towards professionalism; and the lowest mean score was 4.54 which were towards student learning. At Jay Di Pyin high school, the highest mean score of teachers’ competence were 4. 56, which were toward professionalism and the lowest mean score was 4.23, which was regarded as “high” and towards student learning.